Comparison of various alkyl cyanoacrylates for fingerprint development. Issue 1 (2nd January 2017) - Casault, Paméla; Gilbert, Nicolas; Daoust, Benoit
ABSTRACT: The ability of cyanoacrylates (CA) to develop fingerprints was first discovered in 1977. Since then, the cyanoacrylate fuming method has reached widespread use, becoming one of the primary techniques for processing fingerprints. It has, however, almost exclusively been limited to the use of ethyl cyanoacrylate, even though many other alkyl CAs could theoretically be used for this purpose, potentially with a higher efficacy. In order to examine the possibility, cyanoacrylate fuming methods for the processing of fingerprints were optimized for four different CAs: methyl, ethyl, n-butyl and 2-octyl. The development quality and sensitivity yielded by these CAs were then compared using depletion series of natural fingerprints deposited by six donors on three types of surfaces (glass, metal and plastic) and aged during three different periods of time (less than 24h, one week and one month). It was found that, on most age/surface pairs tested, butyl CA produced equivalent or even better results than ethyl CA. Scanning electron microscopy showed that ethyl and butyl CAs generally formed polymer microstructures that scatter light more effectively than methyl and octyl CAs, hence allowing higher visibility of prints processed with these cyanoacrylates.